Quantitative structure activity relationship and molecular docking of antimalarial tricyclic 1,2,4-trioxane derivatives - Koonwadee Ratanasak (Chulalongkorn University, 2006)
Thesis (M.Sc.)--Chulalongkorn University, 2003